Pengaruh Komunikasi, Motivasi Kerja Dan Komitmen Kerja Terhadap Kinerja Karyawan Pada Perusahaan Pelayanan PT Grand Darmo Suite Surabaya - Saviera Hezkia; M. Sihab Ridwan (Jurnal Manajemen Bisnis Era Digital, 2024)
This research discusses the influence of communication, work motivation, and work commitment on employee performance. Effective communication in the workplace plays an important role in building good relationships between managers and employees as well as between employees. High work motivation can increase employee productivity and work quality, while strong work commitment leads to high loyalty and dedication to the organization. This research uses a survey method by distributing questionnaires to employees at the same level from service companies. The collected data is analyzed using statistical techniques such as regression to identify relationships between these variables. The research results show that effective communication significantly contributes to improving employee performance. Work motivation has also been proven to have a strong influence on performance, with employees who feel motivated tending to be more productive and innovative. Apart from that, the level of employee work commitment to the organization also influences their performance positively. Employees who have high levels of commitment tend to show lower levels of absenteeism and greater loyalty to their companies. The implication of these findings is that organizations need to pay attention to and improve internal communication strategies, develop effective work motivation programs, and promote strong work commitment bonds to improve overall employee performance.